ADOPTION AND DIFFUSION OF AGRICULTURAL TECHNOLOGICAL INNOVATIONS GOVERNMENT PROGRAM FIELD SCHOOL INTEGRATED PARTICIPATORY DEVELOPMENT MANAGEMENT OF IRRIGATION PROGRAM (IPDMIP) - Yuni Artanti, Tri (Riviera Publishing, 2023)
This research details efforts to analyze the adoption and diffusion of agricultural technology innovations through the Integrated Participatory Development Management of Irrigation Program (IPDMIP) Field School Program in Kedungreja District, Cilacap Regency. In the background, the urgency of agriculture as the primary sector in development is illustrated, with technology adoption being the key to increasing productivity and farmer welfare. The IPDMIP program emphasizes the involvement of farmers in irrigation management and implementing modern technology to optimize agricultural yields. However, there has not been much in-depth research on the factors that influence the successful adoption and diffusion of technological innovations in the context of this program. This research aims to identify the factors that influence the adoption and diffusion of agricultural technology innovations in the IPDMIP Field School while measuring the adoption and diffusion of these innovations in the Kedungreja District. The quantitative research method uses a survey approach and statistical data analysis. The research instrument includes variables such as cultivated area, farmer age, education level, innovation characteristics, characteristics of potential users, decision-making, communication channels, and instructor qualifications. Data was collected from 100 respondents who were members of farmer groups receiving IPDMIP Field School activities through questionnaires. Data analysis shows that the IPDMIP Field School Program effectively increases the adoption and diffusion of agricultural technology innovations in the Kedungreja District. Factors such as farmer age, characteristics of the innovation, characteristics of potential users, and communication channels play a significant role in the successful adoption and diffusion of the innovation. The research results provide an in-depth picture of the effectiveness of this program in bringing positive change among farmers. This conclusion can be a basis for formulating further policies to support sustainable agricultural development and improve farmer welfare.